Developing a diabetes prevention education program for community health care workers in Thailand: translation of the knowledge to at-risk people - Kitti Sranacharoenpong (2019)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Aim: To evaluate the effects of a randomized education program for community health care workers (CHCWs) on the knowledge, awareness and understanding of key messages related to healthy eating among community members at risk for diabetes (at-risk-DM) identified through community diabetes screening. Subjects and methods: Sixty-nine health centers from five districts in Chiang Mai Province, Thailand, were randomized into the intervention (CHCWs-IG, n = 35) and control group (CHCWs-CG, n = 34). CHCWs-IG participated in a diabetes prevention education program (DPEP) over 4 months. No training/support materials were provided to the CHCWs-CG. The knowledge of all CHCWs was assessed at baseline and the 4- and 8-month follow-ups. To test knowledge dissemination from CHCWs to at-risk-DM, awareness of key messages and other risk factors was tested between at-risk-DM in the CHCW intervention group (at-risk-DM-IG, n = 511) compared with controls (at-risk-DM -CG, n = 405) at baseline and 8 months. Results: CHCWs-IG knowledge scores improved from baseline [mean (SD), 56.5% (6.26)] after 4-month training [75.5% (6.01), p < 0.001] and 8-month follow-up [71.3%(7.36), p < 0.001) while those of CHCW-CG remained unchanged. Body weight, body mass index, waist circumference and systolic blood pressure within at-risk-DM-IG and at-risk-DM-CG at baseline and 8 months were not significantly different. Knowledge test scores of both groups after 8 months had increased from baseline (p = 0.001) but were not different from each other. Conclusion: DPEP for CHCWs was effective in improving knowledge. However, it was likely that multiple influences resulted in improvements in community member knowledge. As expected, no difference between groups in physical measures was observed at 8 months. Long-term lifestyle changes towards the health outcome of diabetes prevention are suggested for future study.